Patient education materials for non-specific low back pain and sciatica: a protocol for a systematic review and meta-analysis. Issue 9 (2nd September 2020) - Furlong, Bradley; Aubrey-Bassler, Kris; Etchegary, Holly; Pike, Andrea; Darmonkow, Georgia; Swab, Michelle; Hall, Amanda
Abstract : Introduction: Low back pain accounts for more disability than any other musculoskeletal condition and is associated with severe economic burden. Patients commonly present with negative beliefs about low back pain and this can have detrimental effects on their health outcomes. Providing evidence-based, patient-centred education that meets patient needs could help address these negative beliefs and alleviate the substantial low back pain burden. The primary aim of this review is to investigate the effectiveness of patient education materials on immediate process, clinical and health system outcomes. Methods and analysis: The search strategy was developed in collaboration with a librarian and systematic searches will be performed in MEDLINE, EMBASE, CINAHL, PsycINFO and SPORTDiscus. We will also search trial registries and grey literature through the OpenGrey database. Study selection will include a title and abstract scan and full-text review by two authors. Only randomised controlled trials will be included in this review. Trials must include patients with low back pain or sciatica and investigate educational interventions with at least one of the following contrasts: (1) education alone versus no intervention; (2) education alone versus another intervention; (3) education in addition to another intervention versus the same intervention with no education. Data extraction, risk of bias and grading of the quality of evidence will be performed independently by two reviewers. Risk of bias will be assessed using the PEDro scale, and the quality of evidence will be assessed with the Grades of Recommendation, Assessment, Development and Evaluation approach. A random-effects model will be used for each contrast, and results will be pooled if the participants, interventions, and outcomes are homogeneous. If heterogeneity is high (I 2 >75%), we will evaluate the magnitude and direction of the differences in effect sizes across studies to determine if it remains reasonable to pool the results. Analyses of acute and subacute low back pain (less than 12 weeks duration) will be performed separately from chronic low back pain (12 weeks or greater duration). Likewise, analyses of short-term (less than 6 months) and long-term (6 months or greater) follow-up will be performed separately. Subgroup analyses will be performed on non-specific low back pain, sciatica and mixed populations. Ethics and dissemination: Ethical approval is not required for this review. This study, along with its results, will be published in a peer-reviewed journal.